2001
DOI: 10.1590/s0100-29452001000200041
|View full text |Cite
|
Sign up to set email alerts
|

Teores De Nutrientes Foliares No Maracujazeiro-Amarelo Associados À Estação Fenológica, Adubação Potássica E Lâminas De Irrigação

Abstract: Conduziu-se um experimento em Campos dos Goytacazes-RJ, para avaliar o efeito da adubação potássica, de lâminas de irrigação e de épocas do ano nos teores de N, P, K, Ca, Mg, S, Zn, Fe, Cu, B, Cl, Mn e Na no maracujazeiro-amarelo (Passiflora edulis f. flavicarpa). Foram testadas, num Argissolo Amarelo distrófico, quatro doses de potássio (76; 307; 531 e 764 g planta-1 ano-1 de K), utilizando o cloreto de potássio, sob seis lâminas de irrigação (0; 25; 50; 75; 100 e 125% da ETo - Evapotranspiração de referência… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
3
18

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 7 publications
3
4
3
18
Order By: Relevance
“…This is in contrast to Mohammad and Athamneh's [26] study about another alternative fertilizer (sewage sludge); they concluded that the lowest iron content was obtained by the control treatment. The iron foliar results with both biofertilizers studied are very much higher than those registered by Carvalho et al [24].…”
Section: Lf Cavalcante Et Alcontrasting
confidence: 68%
See 1 more Smart Citation
“…This is in contrast to Mohammad and Athamneh's [26] study about another alternative fertilizer (sewage sludge); they concluded that the lowest iron content was obtained by the control treatment. The iron foliar results with both biofertilizers studied are very much higher than those registered by Carvalho et al [24].…”
Section: Lf Cavalcante Et Alcontrasting
confidence: 68%
“…Both biofertilizers presented quadratic regression adjustment, although a difference in the peak was registered, i.e., at 1.2 L·plant -1 for enriched biofertilizer and 1.8 L·plant -1 for simple biofertilizer ( figure 2). The copper results of the present study are significantly above the 28.5 mg·kg -1 of Carvalho et al [24] but no visual toxic symptoms were observed.…”
Section: Micronutrientscontrasting
confidence: 55%
“…Em geral, tais fatores são responsáveis pelas variações na composição mineral da cultura (Kliemann et al, 1986;Quaggio & Piza Junior, 1998;Carvalho et al, 2001).…”
Section: Resultsunclassified
“…Em trabalhos desenvolvidos, Carvalho et al (2001) observaram, também, que os teores de Mg nas folhas decresceram com o aumento da quantidade de potássio aplicado via água de irrigação; conforme Prado et al (2004) tal fato ocorreu devido, provavelmente, à competição entre os cátions Mg ++ e K + .…”
Section: Resultsunclassified
See 1 more Smart Citation